Zakochani w słowiku: poezja Józefa Bohdana Zaleskiego w opracowaniu wokalnym Marcelego Madejskiego - Prokopowycz Тetiana (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
The poetry of Józef Bohdan Zaleski (1802–1886) was particularly popular in professional and amateur circles of musicians in mid-nineteenth-century Galicia. The poems of the bright representative of the „Ukrainian school” in Polish literature received a diverse sound frame in chamber and vocal works. The approaches to the selection of poetic texts and their musical interpretation reveal the artistic preferences of the Galician intelligentsia. Literary images of the cultural frontier captured the imagination of the Lviv lawyer Marceli Madejski (1822–1886). The idyllic world of the nightingale land, sung by the poet, became especially close to the amateur composer. M. Madejski’s vocal miniatures „Never”, „Triplets”, „In Love”, „What I Saw”, „Recollection”, „At the Crossroads” reveal a wide range of human feelings, dominated by nostalgia and dream. Musical means express the emotional state of the lyrical hero of Zaleski’s poems.